Expressed needs associated with orthodontic treatment in a private dental college, Mathura - Gaurav Agarwal; Navin Anand Ingle; Navpreet Kaur; Pramod Yadav; Ekta Ingle; Zohra Charania (Wolters Kluwer Medknow Publications, 2015)
Introduction: The primary goal for most of the patients who seek orthodontic treatment is a discernible improvement in some aspect of their dento-facial appearance. Orthodontic therapy makes people look better and feel better about themselves and perhaps influences their ability for social interaction. Hence, this study was conducted to assess expressed needs and barriers associated with orthodontic treatment. Objectives: To know main motivational factor behind seeking orthodontic treatment and to correlate these factors with other variables such as age, gender, and socioeconomic status. Materials and Methods: The study included 200 orthodontic patients between 12 and 25 years visiting a private dental college, Mathura during July 2014 to September 2014. Structured proforma consisting of closed ended questions was used for assessing social demographic characteristics, factors and the barriers, which were associated with orthodontic treatment. Statistical analysis was performed using SPSS version 22. Results: This study comprised of 120 females. Self-confidence (48%) was the main motivating for undergoing treatment among the subjects. Social interaction (44%) was the most common area of improvement expected by the patients after orthodontic treatment. Financial constraints were the main barrier for seeking treatment found among 30% patients. Conclusion: Patients seek orthodontic treatment mainly to enhance facial esthetics, self-confidence and social acceptability. The mismatch of need and desire for treatment is a problem for orthodontists.